2024
DOI: 10.21203/rs.3.rs-4008935/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Mediating Effect of Dark Future between Personality Traits and Fear of Artificial Intelligence in Arab Young Adults

Ali Hemade,
Rabih Hallit,
Diana Malaeb
et al.

Abstract: Background Fear of Autonomous Robots and Artificial Intelligence is a novel concept introduced to measure how fearful individuals are about Artificial Intelligence and autonomous robots. This study aimed to measure the mediating effect of dark future, a measure of future anxiety, between personality traits and Fear of Autonomous Robots and Artificial Intelligence. Methods Using the snowball sampling technique, participants (n = 1839) were Arab adults who completed the Fear of Autonomous Robots and Artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Henceforth, taking into account this looming uncertainty regarding the effects of AI on our future, it is not hard to understand how individuals having elevated levels of future anxiety are more likely to struggle when it comes to accepting this technology, and are therefore more likely to have a negative view of the topic altogether, driven by a fear of upcoming change. This idea is supplemented by a previously mentioned study, conducted on 1839 Arab adults, which suggested that dark future may play an important role in exaggerating the fear felt by a big majority, concerning arti cial intelligence 9 . Moreover, since arti cial intelligence is perceived as a threat, it has been explained in the neuroscience journal how exactly our amygdala responds to this uncertainty, being an emotion that is deeply rooted in innate human mechanisms 42 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Henceforth, taking into account this looming uncertainty regarding the effects of AI on our future, it is not hard to understand how individuals having elevated levels of future anxiety are more likely to struggle when it comes to accepting this technology, and are therefore more likely to have a negative view of the topic altogether, driven by a fear of upcoming change. This idea is supplemented by a previously mentioned study, conducted on 1839 Arab adults, which suggested that dark future may play an important role in exaggerating the fear felt by a big majority, concerning arti cial intelligence 9 . Moreover, since arti cial intelligence is perceived as a threat, it has been explained in the neuroscience journal how exactly our amygdala responds to this uncertainty, being an emotion that is deeply rooted in innate human mechanisms 42 .…”
Section: Discussionmentioning
confidence: 95%
“…In this context, the present study focuses on the relationship between optimism -pessimism and fear of AI. 9 Association between Optimism -Pessimism and Fear of AI Personality traits 9 , including being optimistic or pessimistic 10 , have been suggested as potential factors that could potentially dissect the main causes of distress emanating from the rapidly evolving AI technology. Optimism and pessimism are two perspectives that signi cantly in uence one's view towards the future 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation